What is well-being? A scoping review of the conceptual and operational definitions of occupational well-being - Bautista, Tara G.; Roman, Gretchen; Khan, Munziba; Lee, Michele; Sahbaz, Sumeyra; Duthely, Lunthita M.; Knippenberg, Alexa; Macias-Burgos, Miracle A.; Davidson, Alec; Scaramutti, Carolina; Gabrilove, Janice; Pusek, Susan; et al. (Journal of clinical and translational science, 2023)
Well-being is a multifaceted construct that is used across disciplines to portray a state of wellness, health, and happiness. While aspects of well-being seem universal, how it is depicted in the literature has substantial variation. The aim of this scoping review was to identify conceptual and operational definitions of well-being within the field of occupational health. Broad search terms were used related to well-being and scale/assessment. Inclusion criteria were (1) peer-reviewed articles, (2) published in English, (3) included a measure of well-being in the methods and results section of the article, and (4) empirical paper. The searches resulted in 4394 articles, 3733 articles were excluded by reading the abstract, 661 articles received a full review, and 273 articles were excluded after a full review, leaving 388 articles that met our inclusion criteria and were used to extract well-being assessment information. Many studies did not define well-being or link their conceptual definition to the operational assessment tool being used. There were 158 assessments of well-being represented across studies. Results highlight the lack of a consistent definitions of well-being and standardized measurements.